Priority Criteria and Alternatives for University Business Incubators in the Entrepreneurial Process in Mexico - Lizbeth Martínez Ramírez; Jaime Muñoz (Studia i Materiały)
The Schumpeterian theory of economic development establishes the innovation process as a key factor for entrepreneurship. Nevertheless, not every entrepreneur exercises innovation and not every innovation leads to entrepreneurship. University Business Incubators (UBIs) have been considered as the main factor for entrepreneurial process in which if innovation takes place, the perspective of economic success becomes wide open. Currently, UBIs are typified and considered around the world as guides in the process of entrepreneurship; one of their objectives is the creation of startups that can eventually consolidate in the market. The aim of this work is to identify by means of the Analytic Hierarchy Process (AHP) the priority of UBIs performance criteria on the basis of the main levels of impacts the literature remarks on: a) economic action, b) National Development Plan and/or c) scientific action. These criteria are related with four characteristic UBIs functions: i) provision of means of production, ii) strengthening entrepreneurship culture, iii) bonding with the market to generate a base of future firms, and, iv) creating pull effect. The hypothesis of this work is that UBIs classification not only allows for identifying their main characteristics but it also points toward a normative application of criteria and alternatives of performance, in order to reach the objective of creating and fostering solid and stable enterprises, no matter the sponsoring university characteristics. We tested it by analyzing the three most important Mexican UBIs. The results show that although the analyzed UBIs are a specific type of business incubators, their criteria and alternatives of performance differ among them.